Broadband RCS reduction for electrically-large open-ended cavity using random coding metasurfaces. (4th June 2019) - Zhou, Yang; Yan, Yao; Xie, Jianliang; Chen, Haiyan; Zhang, Guori; Li, Fengxia; Zhang, Li; Wang, Xin; Weng, Xiaolong; Zhou, Peiheng; Li, Xiaoqiu; Deng, Longjiang
Abstract: A scattered radar signal by an electrically-large open-ended cavity involves information of the target. Therefore, controlling the Radar cross section (RCS) of the cavity is significant for target stealth. Coding metasurfaces have promised great possibilities for full control of the electromagnetic waves, especially for reducing RCS by random coding metasurfaces. Here, we report an approach to realize broadband RCS reduction of electrically-large open-ended cavities through loading random coding metasurfaces on the inner side walls. The RCS reduction is caused by suppressing the strong backscattering of corner reflectors inside the cavities, which is further attributed to the diffuse reflection performance of the random coding metasurfaces. Both simulation and measurement show a decrease of cavities RCS, which is a broadband (X-band), polarization-independent, high performance (10 dB) RCS reduction. The proposed method may create new opportunities to improve microwave stealth features of cavities working in high temperatures, which could provide crucial benefits in many practical uses, such as engine nozzles.